Using Multi-user Distributed Virtual Environments in Education - Christos Bouras; Thrasivoulos Tsiatsos; A Philopoulos (World Conference of the WWW, Internet and Intranet- WebNet 2000, San Antonio, Texas, USA, 2000)
On-line learning is one of the emerging needs of the information age. Access to education is going to become crucial for the success of our information society. Therefore a lot of potential is seen in distance learning and distributed virtual environments. The communicative character of the distributed virtual environments would allow for students and stuff to meet in social shared spaces and engage in on-line real-time seminars and tutorials. Such technologies may mitigate some of the problems of isolation that distance learning brings. This paper presents multiuser distributed virtual environments, which are designed and implemented for educational uses.